Head morphology and diet of whiptail catfishes (Loricariidae: Loricariinae) - Silva, Guilherme H. [UNESP]; Zeni, Jaquelini O.; Langeani, Francisco [UNESP] (Sociedade Brasileira de Ictiologia, 2025)
Adaptations in the head structures of fishes can influence food item selection and consumption in aquatic ecosystems. In this study, we tested the relationship between the morphology of the bony structure of the head (suspensorium, mandibular, hyoid, and branchial arches) and the consumption of food items in Loricariinae species. We hypothesize that osteological specializations in the head structures (i.e., mouth) can lead to differential consumption of resources. Despite the relatively high trophic similarity, food item consumption was not uniform among Loricariinae species. The phylogenetic reconstruction recovered morphological patterns already expected for Loricariinae, such as the sister taxa Hemiodontichthys and Reganella. Phylogenetic characters associated with shape, width, and structures in the suspensorium, and branchial arches were correlated with differences in detritus, sediment, and invertebrates consumption. Specifically, branchial arches characters were associated with the consumption of aquatic and terrestrial invertebrates, while suspensorium characters were linked to the consumption of sediment, superior plants, detritus, and aquatic invertebrates. These findings suggest that trophic specialization in loricariines is strongly influenced by the morphological differentiation of these structural features.

Adaptações nas estruturas bucais dos peixes podem influenciar a seleção e o consumo de itens alimentares nos ecossistemas aquáticos. Neste estudo, testamos a relação entre a morfologia de estruturas ósseas do crânio (suspensório, arco mandibular, arco hioide e arcos branquiais) e o consumo de itens alimentares em Loricariinae. Nossa hipótese é que especializações osteológicas nas estruturas do crânio (i.e., boca) podem levar a um consumo diferenciado de recursos alimentares. Apesar da similaridade trófica relativamente alta, o padrão de consumo de itens alimentares não foi uniforme entre as espécies de Loricariinae. A reconstrução filogenética recuperou padrões morfológicos já esperados para Loricariinae, como os táxons irmãos Hemiodontichthys e Reganella. Caracteres filogenéticos associados à forma, largura e estruturas no suspensório e nos arcos branquiais foram correlacionados com diferenças no consumo de detritos, sedimentos e invertebrados. Em particular, os caracteres dos arcos branquiais foram associados ao consumo de invertebrados aquáticos e terrestres, enquanto os caracteres do suspensório foram associados ao consumo de sedimentos, plantas superiores, detritos e invertebrados aquáticos. Essas descobertas sugerem que a especialização trófica em loricaríneos é fortemente influenciada pela diferenciação morfológica dessas características estruturais.
Keywords: Aquatic invertebrates; Branchial arches; Osteology; Suspensorium; Trophic ecology; Arcos branquiais; Ecologia trófica; Invertebrados aquáticos; Osteologia; Suspensório